The insider's guide to legal skills - Allbon, Emily; Kaur Dua,Sanmeet (New York: Routledge, 2023)
'Confused by cases? Stuck on statutes? Or just unsure where to start with writing, research or revision? The Insider's Guide to Legal Skills will show you what you need to succeed, applying skills in their real-world context and helping you get to grips with legal method and thinking. Making use of problem-based learning and examples throughout, the fully updated second edition of this practical and accessible guide will provide you with a clear guide to skills within the law degree and how to make the most of them in assessment, but also help you to see their importance to a future legal career. Designed for LLB/GDL students who want a clear overview of what a law degree is all about, the book has been built on the skills curriculum, and is a suitable text for Legal Skills, Methods and Reasoning courses as well as a general introduction to law, or pre-reading for those considering a law degree'--
Meet our friends ... -- Academic survival skills : standing on your own two feet -- Your guide to the English legal system : order order -- Legal research : digging deeper -- Legal writing : weaning off'like' and'innit' -- Referencing and plagiarism : borrow don't steal -- Mooting and public speaking : speaker's corner -- Employability : learn to earn -- Revision and exams : law, eat, sleep, repeat.
Includes bibliographical references and index. (236-244 pages)
Puan Shaizimah Badzri (Bacaan Asas FUU)/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ 0389216390/ OC/ Bookline Services
Keywords: Law -- Vocational guidance -- Great Britain; Legal composition; Practice of law -- Great Britain -- Problems, exercises, etc